MENGEMBALIKAN MEMORI KAMPUNG TUGU MELALUI RUANG KEBUDAYAAN KAMPUNG TUGU, JAKARTA - Feris Misael Trifosa; Sutarki Sutisna (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Kampung Tugu area is a cultural heritage area. The Tugu Church, the Portuguese Village, the Rabo-Rabo Tradition, Mande-Mande as well as the Keroncong and Tugu dances are regional characters that are reflected in the Tugu Village. The area has undergone environmental changes, where village land use is currently mostly used as container and industrial parking lots which has caused the character of the Kampung Tugu area to slowly disappear, Kampung Tugu has become an intangible memory. Urban acupuncture is a strategy in placing cultural activity points as an effort to cure diseases in the area. Using everyday methods and typologies in the design can connect the needs of the area to the project to become a continuation of existence and revive the character of the Kampung Tugu area. Rabonde Toegoe is a new face for Kampung Tugu, a living tourism of Portuguese and Betawi culture that Tugu has. The design is carried out with adaptive reuse for the Tugu community in maintaining culture and opening up space to become an attraction for outsiders. Keywords:  acupuncture; architecture; character; city; degradation; region Abstrak Kawasan Kampung Tugu merupakan kawasan cagar budaya. Gereja Tugu, Kampung Portugis, Tradisi Rabo-Rabo, Mande-Mande serta Keroncong dan tarian Tugu, merupakan karakter kawasan yang tergambar dari Kampung Tugu. Kawasan mengalami perubahan secara lingkungan, dimana penggunaan lahan kampung, saat ini mayoritas digunakan sebagai lahan parkir kontainer dan industri yang menyebabkan karakter kawasan Kampung Tugu perlahan hilang, Kampung Tugu menjadi sebuah memori yang tidak berwujud. Akupunktur perkotaan menjadi sebuah strategi dalam menempatkan titik - titik aktivitas budaya sebagai upaya penyembuhan terhadap penyakit pada kawasan. Dengan menggunakan metode keseharian dan tipologi pada perancangan dapat mengkoneksikan kebutuhan kawasan terhadap proyek untuk menjadi sebuah kelanjutan dari eksistensi dan menghidupkan karakter kawasan Kampung Tugu. Rabonde Toegoe menjadi wajah baru bagi Kampung Tugu menjadi wisata hidup kebudayaan Portugis dan Betawi yang Tugu miliki. Perancangan dilakukan dengan penggunaan kembali secara adaptif bagi komunitas Tugu dalam mempertahankan kebudayaan serta membuka ruang untuk menjadi daya tarik bagi masyarakat luar.